Cross‐section modified and highly elastic sutures reduce tissue incision and show comparable biocompatibility: in‐vitro and in‐vivo evaluation of novel thermoplastic urethane surgical threads. Issue 5 (24th October 2020) - Helmedag, Marius; Heise, Daniel; Eickhoff, Roman; Kossel, Klas‐Moritz; Gries, Thomas; Jockenhoevel, Stefan; Neumann, Ulf Peter; Klink, Christian Daniel; Lambertz, Andreas
Abstract: Surgical sutures are indispensable for a vast majority of operative procedures. An ideal suture is characterized by high tissue compliance without cutting into the mended tissue and optimal biocompatibility. Therefore, we assessed these mechanical and biological properties for novel elastic thermoplastic polyurethane (TPU) and cross‐sectional modified "snowflake" sutures. Circular and "snowflake"‐shaped TPU threads were manufactured and compared to similar surface modified polyvinylidene fluoride (PVDF) sutures. Regular PVDF sutures were used as the control group. Single‐axis tensile test with and without gelatinous tissue surrogates were performed to evaluate the suture incision into the specimens. Biocompatibility was evaluated by subcutaneous implantation ( n = 18) in rats for 7 and 21 days. Histology and immunohistology was conducted for assessment of the foreign body reaction. Regular and modified TPU threads showed a significant reduction of incision into the tissue surrogates compared to the control. Both TPU sutures and the modified PVDF sutures achieved comparable biocompatibility versus regular PVDF threads. Detailed histology revealed novel tissue integration into the notches of the surface modified sutures, we termed this newly shaped granuloma "intrafilamentous" granuloma. Elastic TPU threads showed a significant reduction of tissue surrogate incision and suture tension loss. Biocompatibility did not significantly differ from standard PVDF. Histology demonstrated tissue ingrowth following the surface modification of the suture referred to as "intrafilamentous" granuloma. Further in vivo studies are required to illuminate the exact potential of the new sutures to optimize intestinal anastomosis.